FIRST DISCINID BRACHIOPODS (BRACHIOPODA: LINGULIDA) FROM THE CENOZOIC OF PATAGONIA (GAIMAN FORMATION, LOWER MIOCENE, ARGENTINA) (Ameghiniana, 2023)
Discinids are a group of inarticulate brachiopods with organophosphatic shells and a very poor fossil record. we report for the first time the presence of this family in the Cenozoic of Patagonia, represented by two new species: Discinisca porvenir sp. nov. and Discinisca messii sp. nov., both found in marine deposits of the Gaiman Formation (Lower Miocene) in Chubut province, Argentina. Specimens come from four localities: Bryn Gwyn, Cañadón del Puma, Isla Escondida, and Punta Loma. The first species, D. porvenir sp. nov., presents a shell with subcircular to subtrapezoidal outline in dorsal view and maximum width located slightly anterior, apex near to the last quarter of the total valve length, and external sculpture formed by narrow concentric bands with irregular edges. In contrast, the second species, D. messii sp. nov., shows a valve with subcircular to circular outline in dorsal view with apex placed near to posterior margin, and external sculpture formed by concentric bands with a rounded triangular profile in transverse section. The new species seem to be related to the living D. lamellosa and D. laevis, respectively, both with a western South American distribution. The Gaiman Formation includes phosphatic nodules and abundant cases of well-preserved phosphatic vertebrate remains. Due to this, and the biostratinomic conditions deduced for vertebrates, the preservation of the brachiopods could be favoured.